4D flow MRI and T1‐Mapping: Assessment of altered cardiac hemodynamics and extracellular volume fraction in hypertrophic cardiomyopathy. Issue 1 (31st July 2015) - van Ooij, Pim; Allen, Bradley D.; Contaldi, Carla; Garcia, Julio; Collins, Jeremy; Carr, James; Choudhury, Lubna; Bonow, Robert O.; Barker, Alex J.; Markl, Michael
Abstract : Purpose: Hypertrophic cardiomyopathy (HCM) is associated with altered hemodynamics in the left ventricular outflow tract (LVOT) and myocardial tissue abnormalities such as fibrosis. The aim of this study was to quantify changes in LVOT 3D hemodynamics and myocardial extracellular volume fraction (ECV, measure of fibrosis) and to investigate relationships between elevated flow metrics and left ventricular (LV) tissue abnormalities. Materials and Methods: Cardiac magnetic resonance imaging (MRI) including 4D flow (field strength = 1.5T, resolution = 2.1–4.0 × 2.1–4.0 × 2.5–3.2 mm 3 ; venc = 150–250 cm/s; TE/TR/FA = 2.2–2.5msec/4.6–4.9msec/15°) for the in vivo assessment of 3D blood flow velocities with full coverage of the LVOT was applied in 35 patients with HCM (54 ± 15 years) and 10 age‐matched healthy controls (45 ± 14 years). In addition, pre‐ and postcontrast myocardial T 1 ‐mapping (resolution = 2.3 × 1.8 mm, slice thickness = 8 mm, TE/TR‐FA = 1.0‐1.1msec/2.0‐2.2msec/35°) of the LV (basal, mid‐ventricular, apical short axis) was performed in a subgroup of 23 HCM patients. Analysis included the segmentation of the LVOT and quantification of peak systolic LVOT pressure gradients and rate of viscous energy loss EL ′ as well as left ventricular ECV. Results: HCM patients demonstrated significantly elevated peak systolic LVOT pressure gradients (21 ± 16 mmHg vs. 9 ± 2 mmHg) and energy loss EL ′ (3.8 ± 2.5 mW vs. 1.5 ± 0.7 mW, P < 0.005) compared to controls. There was a significant relationship between increased LV fibrosis (ECV) with both elevated pressure gradients (R 2 = 0.44, P < 0.001) and energy loss EL ′ (R 2 = 0.46, P < 0.001). Conclusions: The integration of 4D‐flow and T 1 ‐mapping‐MRI allowed for the evaluation of tissue and flow abnormalities in HCM patients. Our findings suggest a mechanistic link between abnormal LVOT flow, increased LV loading, and adverse myocardial remodeling in HCM. J. MAGN. RESON. IMAGING 2016;43:107–114.